An Online Database to Improve Clinical Operations and Scientific Data Collection in a Pediatric Hearing Loss Practice. Issue 5 (June 2015) - Formeister, Eric J.; Forgues, Mathieu; Adunka, Oliver F.
<x xml:space="preserve">Abstract</x> Objective To establish a pediatric hearing loss database that improves scientific data collection and clinical workflow in a large pediatric hearing loss and cochlear implant practice and incentivizes users to maintain careful scientific data collection and entry. Patients All children with hearing loss referred to the study institution. Intervention A multiuser multistation database was designed using a commercial database solution. Electronic data previously available were imported and verified. Various groups of professionals were educated on proper data entry methods. The database incorporated clinical information used in daily practice to ensure routine data entry and verification. Main Outcome Measures Number of children entered into the database; user feedback on database feasibility; longitudinal speech perception performance in implanted children. Results Data import proved labor intensive but feasible. New data entry was facilitated by the instrument's usefulness in daily practice, which was readily accepted by the team involved in the management of pediatric hearing loss. Currently, the database includes more than 2, 900 pediatric patients with hearing im pairment, of which 1, 034 have cochlear implants. Files contain audiometric, speech, anatomic, and surgical data. Speech perception performance increased with increasing age and duration of cochlear implant use for 478 children with speech perception data. Conclusion The present database offers a powerful tool for scientific data collection and was easily integrated into the institution's busy clinical practice as a minimally time-consuming task. Database use facilitated querying for easy application to a number of clinical studies from this institution.